Impact of intrafraction changes in delivered dose of the day for prostate cancer patients treated with stereotactic body radiotherapy via MR-Linac. (September 2022) - Dang, Jennifer; Kong, Vickie; Li, Winnie; Navarro, Inmaculada; Winter, Jeff D.; Malkov, Victor; Berlin, Alejandro; Catton, Charles; Padayachee, Jerusha; Raman, Srinivas; Warde, Padraig; Chung, Peter
Highlights: Beam on MR acquisition on the MR-Linac can be used to compute DDOTD. Intrafraction motion via volumetric variability of OARs can impact dosimetry. Computation of the DDOTD may help inform prospective fractions for SBRT prostate. Abstract: Purpose: The purpose of this study is to evaluate the impact of intrafraction pelvic motion by comparing the adapted plan dose (APD) and the computed delivered dose of the day (DDOTD) for patients with prostate cancer (PCa) treated with SBRT on the MR-Linac. Methods: Twenty patients with PCa treated with MR-guided adaptive SBRT were included. A 9-field IMRT distribution was adapted based on the anatomy of the day to deliver a total prescription dose of 3000 cGy in 5 fractions to the prostate plus a 5 mm isotropic margin. Prostate, bladder, and rectum were re-contoured on the MR-image acquired during treatment delivery (MRBO ). DDOTD was computed by propagating the dose from the daily adapted plan generated during treatment onto the MRBO . Results: Target coverage was met for all fractions, however, computed DDOTD was significantly less than the APD (p < 0.05). During an average treatment of 53 min, mean bladder volume increased by 116%, which led to a significant decrease in the DDOTD bladder D40% (p < 0.001). However, DDOTD to bladder 5 cc was significantly higher (p < 0.001) than APD. Rectum intrafraction changes were observed based on a volume change of −20% to 83% and presence of significant dose changes from APD to DDOTD for rectum D20% (p < 0.05) and D1cc (p < 0.0001). Conclusions: Intrafraction motion observed during prostate SBRT treatment on the MR-Linac have dosimetric impacts on both the target and organs at risk. Post-treatment computation using DDOTD may inform adaptation beyond anatomic changes in subsequent treatment fractions to best capitalize on MR-Linac technology and widen the therapeutic index of SBRT for PCa.